GE_GERICHTE P/5612/2009 vom 10. April 2012 - GE Cour de justice (2012)
CONDITION DE RECEVABILITÉ; PRÉVENU; EXTENSION DE LA PROCÉDURE; OBJET DU RECOURS; DÉCISION; COMPÉTENCE RATIONE MATERIAE | CPP.111; CPP.311; CPP.393; CPP.109